A distance-running event and life satisfaction: The mediating roles of involvement. Issue 5 (November 2016) - Sato, Mikihiro; Jordan, Jeremy S.; Funk, Daniel C.
Highlights: We examined the effects of a running event on participants' life satisfaction. A sample of 742 participants was recruited from a 10 mile distance-run in the U.S. Participation in the event was positively associated with weekly running activity. Pleasure and sign mediated the link between running activity and life satisfaction. Abstract: The increasing popularity of mass participant sport events has provided sport event managers and scholars with an opportunity to contribute to a broader conversation on ways to promote population health. Theoretically, these managed sport services should have the capacity to enhance event participants' well-being; however, the empirical link between event participation and well-being remains inconclusive. By comparing individuals who participated in a distance-running event with individuals who did not participate in the event, this study examined the contributions of the distance-running event, behavioural loyalty, and psychological involvement to life satisfaction, an indicator of mental health and well-being. Participants ( N  = 742) were recruited from a 10-mile running event held in the United States. The results revealed that participation in a distance-running event was positively associated with weekly running activity, an indicator of behavioural loyalty. In addition, the two facets of psychological involvement in running—pleasure and sign—mediated the relationship between weekly running activity and life satisfaction. These findings provide empirical support that distance-running events can serve as environmental correlates of participants' behavioural loyalty and that the contribution of behavioural loyalty to life satisfaction lies in whether event participants identify pleasant and symbolic aspects of the activity.